Development of PID and Fuzzy Control Strategies for Navigation in Agricultural Environments - Bonadies S; Smith N; Niewoehner N; Lee A; Lefcourt AM; Gadsden SA (ASME International, 2018)
Farming and agriculture is an area that may benefit from improved use of automation in order to increase working hours and improve food quality and safety. In this paper, a commercial robot was purchased and modified, and crop row navigational software was developed to allow the ground-based robot to autonomously navigate a crop row setting. A proportional-integral-derivative (PID) controller and a fuzzy logic controller were developed to compare the efficacy of each controller based on which controller navigated the crop row more reliably. Results of the testing indicate that both controllers perform well, with some differences depending on the scenario.
Keywords: 40 Engineering; 2 Zero Hunger